Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please only give hints? $$\lim_{x \to \frac{\pi}{6}}\frac{2\sin{(x)}-1}{\sqrt{3}\tan{(x)}-1}$$ I tried this and I was able to simplify it down to $$\lim_{x \to \frac{\pi}{6}}\frac{\sin{(2x)}-\cos{(x)}}{2\sin{(x - \frac{\pi}{6})}}.$$ However, I am stuck here and I don't even know if this is the right approach. Thanks!

share|cite|improve this question
up vote 1 down vote accepted

$$F=\frac{2\sin{(x)}-1}{\sqrt{3}\tan{(x)}-1} =\frac2{\sqrt3}\cdot\frac{\sin x-\sin \frac\pi6}{\tan x-\tan\frac\pi6} =\frac2{\sqrt3}\cdot\frac{2\sin \left(\frac{x-\frac\pi6}2\right)\cos \left(\frac{x+\frac\pi6}2\right)}{\tan x-\tan\frac\pi6}$$ (Applying $\sin C-\sin D=2\sin\frac{C-D}2\cos\frac{C+D}2$)

Now, $$\tan x-\tan\frac\pi6 =\frac{\sin \left(x-\frac\pi6\right)}{\cos x\cos\frac\pi6}=\frac{2\sin \left(\frac{x-\frac\pi6}2\right)\cos\left(\frac{x-\frac\pi6}2\right)}{\cos x\cos\frac\pi6}$$

So, $$F=\frac2{\sqrt3} \cos x\cos\frac\pi6\frac{2\sin \left(\frac{x-\frac\pi6}2\right)\cos\left(\frac{x+\frac\pi6}2\right)}{2\sin \left(\frac{x-\frac\pi6}2\right)\cos\left(\frac{x-\frac\pi6}2\right)}$$

If $x\to\frac\pi6, \sin \left(\frac{x-\frac\pi6}2\right)\to0\implies \sin \left(\frac{x-\frac\pi6}2\right)\ne0$

So, $$\lim_{x\to\frac\pi6}F=\lim_{x\to\frac\pi6}\frac2{\sqrt3} \cos x\cos\frac\pi6\frac{\cos\left(\frac{x+\frac\pi6}2\right)}{\cos\left(\frac{x-\frac\pi6}2\right)}=\frac2{\sqrt3} \cos \frac\pi6\cos\frac\pi6 \frac{\cos\frac\pi6}{\cos0}=\frac34$$

share|cite|improve this answer
Thanks, very nice solution. How did you come up with this tho? How did you know that this complex sequence of steps would lead you to the answer? Did it take you a long time? – Ovi May 7 '13 at 22:58
@Ovi, I've observed the Singularity at $x=\frac\pi6\implies \sin \left(\frac{x-\frac\pi6}2\right)=0$ there. Please find my other answer.Hope that is simpler. – lab bhattacharjee May 8 '13 at 4:53

Hint: $\sin(2x)=2\sin x \cos x$

share|cite|improve this answer
Haha more hints please? – Ovi May 6 '13 at 23:44
I don't see how this really helps – Ethan May 6 '13 at 23:47
Yea the only thing you can do after that is factor out the cos(x) but I don't see how that helps – Ovi May 6 '13 at 23:47

Another hint: Try using L'Hôpital's rule. If you plug $\displaystyle \frac{\pi}{6}$ into the original limit, you'll see that it evaluates to an indeterminate $\displaystyle \frac{0}{0}$. Use that and the rule, and you should be able to solve for the limit.

share|cite|improve this answer
Is there really no other way? – Ovi May 6 '13 at 23:54
Well, this is one of the simpler methods. I suppose you could try reorganizing the limit... – Marvon May 6 '13 at 23:57
Well yea I'm trying to do that but I'm kindda stuck. – Ovi May 7 '13 at 0:06
Which part? Do you need some help with the differentiation steps for the top and bottom parts? – Marvon May 7 '13 at 0:20
No I meant I was trying to reorganize the limit and solve it without L'Hopital's rule – Ovi May 7 '13 at 0:22

Note that $$\dfrac{2 \sin(x)-1}{\sqrt3 \tan(x) - 1} = \dfrac2{\sqrt3} \left(\dfrac{\sin(x)-1/2}{\tan(x)-1/\sqrt{3}} \right) = \dfrac2{\sqrt3} \dfrac{\dfrac{\sin(x)-\sin(\pi/6)}{x-\pi/6}}{\dfrac{\tan(x)-\tan(\pi/6)}{x-\pi/6}}$$

share|cite|improve this answer
Oh thanks I see so now it's just the derivative of sin x at pi/6 over the derivative of the tangent. Thanks – Ovi May 7 '13 at 0:20
Wait I thought that it would just be $cos(pi/6)/sec^2(pi/6)$. However, this gives you 3sqrt(3)/8, and the correct answer is 3/4. – Ovi May 7 '13 at 0:27
@Ovi There is a $\dfrac2{\sqrt3}$ multiplying it. – user17762 May 7 '13 at 0:31
Haha ok thanks I completely missed that – Ovi May 7 '13 at 0:31

Hint: L'Hopital's Rule right at the beginning

share|cite|improve this answer
Is there really no other way? – Ovi May 6 '13 at 23:54

Putting $x=\frac\pi6-y$ as $x\to\frac\pi6,y\to0$

$$2\sin x-1=2\sin(\frac\pi6-y)-1=\cos y-\sqrt3\sin y-1$$

$$\sqrt3\tan x-1=\sqrt3\tan(\frac\pi6-y)-1=\sqrt3\cdot \frac{\frac1{\sqrt3}-\tan y}{1+\tan y\frac1{\sqrt3}}-1$$ $$=\sqrt3\cdot\frac{1-\sqrt3\tan y}{\sqrt3+\tan y}-1=\frac{\sqrt3-3\tan y}{\sqrt3+\tan y}-1=\frac{-4\tan y}{\sqrt3+\tan y}$$

$$\text{So,}\frac{2\sin x-1}{\sqrt3\tan x-1}=\frac{(\cos y-\sqrt3\sin y-1)(\sqrt3+\tan y)}{-4\tan y}$$ $$=\frac14\cdot(\sqrt3+\tan y)\cdot\left(\sqrt3\frac{\sin y}{\tan y}+\frac{1-\cos y}{\tan y} \right)$$

$$\text{So,}\lim_{x\to\frac\pi6}\frac{2\sin x-1}{\sqrt3\tan x-1}$$

$$=\lim_{y\to0}\frac14\cdot(\sqrt3+\tan y)\cdot\left(\sqrt3\frac{\sin y}{\tan y}+\frac{1-\cos y}{\tan y} \right)$$

$$= \frac14\cdot\lim_{y\to0}(\sqrt3+\tan y)\cdot\left(\sqrt3 \cdot\lim_{y\to0}\frac{\sin y}{\tan y}+\lim_{y\to0}\frac{\sin^2y\cdot\cos y}{\sin y(1+\cos y)} \right)$$ $$=\frac14\cdot(\sqrt3+0)\cdot\left(\lim_{y\to0}\sqrt3\cos y+\lim_{y\to0}\frac{\sin y\cdot\cos y}{1+\cos y} \right)$$ as $y\to0,\sin y\to 0\implies \sin y\ne0$


share|cite|improve this answer
@Ovi, is this simpler than my other answer? – lab bhattacharjee May 11 '13 at 5:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.